Mechanism of gypsum hydration - Pacheco, G.; Portilla, M. (Materiales de Construcción, 1991)
There is an hypothesis that the mechanism o f gypsum hydration and dehydration is performed through two simultaneous phenomena. In this study we try to clear up this phenomenon using chlorides as accelerators or a mixture of ethanol-methanol as retarders to carry out the gypsum setting. Natural Mexican gypsum samples and a hemihydrate prepared in the laboratory are used. The following analytical techniques are used: MO, DRX, DTA, TG and DTG. In agreement with the obtained results, it can be concluded: that colloid formation depends on the action of accelerators or retarders and the crystals are a consequence of the quantity of hemihydrate formed.